CO-promoted polyethylene hydrogenolysis with renewable formic acid as hydrogen donor - Yuqi Wang; Qikun Hu; Shuairen Qian; Jiayang Zhao; Yi Cheng; Jun Ma; Jing Zhang; Zhiqiang Niu (Nature Communications)
Abstract Hydrogenolysis has emerged as a promising strategy for the chemical recycling of plastic waste, yet its reliance on high-pressure hydrogen poses significant challenges. Biomass- or CO2-derived formic acid (FA) is a renewable hydrogen carrier with the advantages of low toxicity and ease of storage and transport. Here, we use FA to replace high-pressure hydrogen to convert polyethylene (PE) into fuels and chemicals with only 4.1% gaseous products by a RuPt alloy catalyst. We demonstrate that the trace amounts of CO generated from the decomposition of FA do not poison the active sites, but rather induce the formation of Ruδ+, which facilitates the C–C bond cleavage during PE hydrogenolysis. This approach eliminates the need for high-pressure hydrogen and provides a more flexible and adaptable approach for decentralized plastic processing.